DNA microarrays : a practical approach - Schena, Mark (Oxford University Press, 2000)
Written and edited by experts in the field, this book provides valuable insight into the remarkable advancement of DNA microarrays. It is essential for researchers investigating patterns of gene expression and useful for all those interested in the use of biochips.
Practical Approach Series
Keywords: Genetics; Genom; genetika, lékařská genetika; klinické laboratorní techniky; DNA; Laboratorní technika; Clinical Laboratory Techniques; genom; Genome; genetika